Faculty Perception of a Multidisciplinary Experience: Art and Science in an Education Degree Program - Folch, Carmina (2019)
This article presents an experience carried out by the faculty of the third year of the Infant Education degree at the Ramon Llull University in Barcelona (Spain). A proposal for multidisciplinary intervention that joins two modules: one for arts (musical, corporal, visual, and plastic education) and another for sciences (mathematics, and experimental and social sciences). The intervention stems from a generating idea—the book “Alice in Wonderland”—which allows for connections between the contents of the modules, involves co-teaching, multidisciplinary work, and shared evaluation experiences. The aim of the study is to get to know the perception of the participating faculty about the changes in the didactic components involved in the experience. For data collection, semi-structured interviews were carried out at three moments of the process and a discussion group at the end. The analysis of the data shows that the experience has been rich in terms of the multidisciplinary approach, shared teaching, growth of creative competence, the student´s cooperative work and leadership capacity. Weaknesses reside in the assessment process and difficulties finding adequate time and space to prepare and implement the proposal.